Genome-wide meta-analysis identifies novel determinants of circulating serum progranulin. (27th November 2017) - Tönjes, Anke; Scholz, Markus; Krüger, Jacqueline; Krause, Kerstin; Schleinitz, Dorit; Kirsten, Holger; Gebhardt, Claudia; Marzi, Carola; Grallert, Harald; Ladenvall, Claes; Heyne, Henrike; Laurila, Esa; et al.
Abstract: Progranulin is a secreted protein with important functions in processes including immune and inflammatory response, metabolism and embryonic development. The present study aimed at identification of genetic factors determining progranulin concentrations. We conducted a genome-wide association meta-analysis for serum progranulin in three independent cohorts from Europe: Sorbs ( N =  848) and KORA ( N =  1628) from Germany and PPP-Botnia ( N =  335) from Finland (total N =  2811). Single nucleotide polymorphisms (SNPs) associated with progranulin levels were replicated in two additional German cohorts: LIFE-Heart Study (Leipzig; N =  967) and Metabolic Syndrome Berlin Potsdam (Berlin cohort; N =  833). We measured mRNA expression of genes in peripheral blood mononuclear cells (PBMC) by micro-arrays and performed mRNA expression quantitative trait and expression-progranulin association studies to functionally substantiate identified loci. Finally, we conducted siRNA silencing experiments in vitro to validate potential candidate genes within the associated loci. Heritability of circulating progranulin levels was estimated at 31.8% and 26.1% in the Sorbs and LIFE-Heart cohort, respectively. SNPs at three loci reached study-wide significance (rs660240 in CELSR2-PSRC1-MYBPHL-SORT1, rs4747197 in CDH23-PSAP and rs5848 in GRN ) explaining 19.4%/15.0% of the variance and 61%/57% of total heritability in the Sorbs/LIFE-Heart Study. The strongest evidence for association was at rs660240 ( P =  5.75 × 10 −50 ), which was also associated with mRNA expression of PSRC1 in PBMC ( P =  1.51 × 10 −21 ). Psrc1 knockdown in murine preadipocytes led to a consecutive 30% reduction in progranulin secretion. In conclusion, the present meta-GWAS combined with mRNA expression identified three loci associated with progranulin and supports the role of PSRC1 in the regulation of progranulin secretion.